3y2-2=-110

Add 2 to both sides of the equation.

3y2=-110+2

Add -110 and 2.

3y2=-108

3y2=-108

Divide each term in 3y2=-108 by 3.

3y23=-1083

Cancel the common factor of 3.

Cancel the common factor.

3y23=-1083

Divide y2 by 1.

y2=-1083

y2=-1083

Divide -108 by 3.

y2=-36

y2=-36

Take the square root of both sides of the equation to eliminate the exponent on the left side.

y=±-36

Simplify the right side of the equation.

Rewrite -36 as -1(36).

y=±-1⋅36

Rewrite -1(36) as -1⋅36.

y=±-1⋅36

Rewrite -1 as i.

y=±i⋅36

Rewrite 36 as 62.

y=±i⋅62

Pull terms out from under the radical, assuming positive real numbers.

y=±i⋅6

Move 6 to the left of i.

y=±6i

y=±6i

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

y=6i

Next, use the negative value of the ± to find the second solution.

y=-6i

The complete solution is the result of both the positive and negative portions of the solution.

y=6i,-6i

y=6i,-6i

y=6i,-6i

Solve for y 3y^2-2=-110